Figuren des Messianischen in Schriften deutsch-jüdischer Intellektueller 1900-1933 - Dubbels, Elke (Conditio Judaica, 2011)
This study investigates the function of the recourse to the messianic tradition of Judaism among German-Jewish intellectuals in the first third of the 20th century. Messianic figures of thought play an important role in the Jewish discourse of identity. Moreover, they are used productively in the creation of general theories in the realm of cultural studies, especially regarding the philosophy of language and history and the theological-political complex. Here, all the considered authors (Benjamin, Bloch, Broch, Buber, Landauer, Rosenzweig, Scholem) secularize Jewish Messianism in one way or another, thus transforming the Messiah into the messianic. This also means, however, that the messianic figures of speech include not only figures of thought but also rhetorical figures of speech or tropes that reflect various constellations of sacrality and secularity in the modern era. Tension between the secular and the sacred, and also between cultural particularity and universality, forms part of the modern adaptation of Jewish Messianism, as does the possibility of a sudden dialectical critical shift to an affirmation of violence.